Transitions of Care Coordination Intervention Identifies Barriers to Discharge in Hospitalized Stroke Patients - Zimmerman, William Denney; Grenier, Rachel E.; Palka, Sydney V.; Monacci, Kelsey J.; Lantzy, Amanda K.; Leutbecker, Jacqueline A.; Geng, Xue; Denny, Mary Carter (Frontiers in Neurology, 2021)
Background: Prolonged hospital lengths of stay increase costs, delay rehabilitation, and expose acute ischemic stroke patients to hospital-acquired infections. We designed and implemented a nurse-driven, Transitions of Care Coordinator (TOCC) program to facilitate the transition of care from the acute care hospital setting to rehabilitation centers and home. Methods: The intervention consisted of a stroke nurse navigator completing specific tasks, including meeting with stroke patients and their families, facilitating communication between team members at multi-disciplinary rounds, assisting with referrals to rehabilitation facilities, providing stroke education, and arranging stroke clinic follow-up appointments. The primary outcome was to assess the feasibility of the program. Secondary outcomes included comparing hospital length of stay (LOS) and patient satisfaction between the TOCC and usual care groups. Results: The TOCC program was feasible with all components completed in 84% of stroke patients. There was no significant difference in LOS between the two groups. There was a trend toward higher patient satisfaction in the TOCC group. The TOCC study allowed us to identify patient variables (gender, insurance, stroke severity and discharge disposition) that were associated with prolonged hospitalizations. Conclusion: A TOCC program is feasible and can serve as a guide for future allocation of resources to facilitate transitions of care and avoid prolonged hospital stays.